ANALISIS LINGKUNGAN FISIK UDARA TERHADAP ANGKA KUMAN UDARA DI RUMAH SAKIT - Andari Mayasari; Zulkarnain Zulkarnain; Agrina Agrina (Jurnal Ilmu Lingkungan, 2019)
Compounds that are often used by society in controlling fly populations are chemical insecticides. Inappropriate use of chemical insecticides will harm the environment and human health directly and long term, such as poisoning, respiratory disorders, resistance to insects and environmental pollution. One other alternative to control house flies is organic insecticide that it is basic ingredients come from nature. The purposes of this study were for analyze the effectiveness of organic insecticides in controlling house fly vectors, to determine the concentration of LC 50% organic insecticides to house flies and to find out the impact of organic insecticides on environmental and economic aspects. This study used an experimental method and a completely randomized design (CRD) with four different treatments, namely control, 10% betel leaf extract + 4 ml EM4, 20% betel leaf extract + 4 ml EM4 and 30% betel leaf extract + 4 ml EM4. Each treatment was carried out with three replications. The results of the analysis showed the least amount of mortality of house fly in the control treatment ie one house fly, while the highest average of house flies mortality are 30% betel leaf extract treatment + 4 ml EM4 that are 8.66 house flies. Based on the ANOVA test, the p value <0.05 was concluded that the mean of the four research treatments differed significantly. Based on probit analysis, it was found that the concentration of LC 50% in house flies was 13.09%. Organic insecticide in terms of environment and economy has a positive impact, it can reduce odor in organic waste and has economic value compared to chemical insecticides.